Influence of Alcohol and Cognitive Capacity on Visual Number Judgements. (January 2021) - Harvey, Alistair J.; Seedhouse, Molly
We used an enumeration task to address the question of whether acute alcohol intoxication reduces cognitive or perceptual capacity. To control for individual differences in cognitive resources, we took a sober record of each participant's working memory capacity (WMC). Alcohol was expected to impair enumeration performance, either for the automatic parallel counting of small stimulus sets indicating a perceptual impairment, or the controlled counting or estimating of larger sets indicating a cognitive impairment. Enumeration showed an overall decline in accuracy following a vodka beverage and the deficit was negligible for small sets, which is inconsistent with a loss of perceptual capacity. Having a higher WMC facilitated the enumeration of larger sets and the correlation between WMC and accuracy was stronger in the alcohol condition suggesting that low-WMC participants were more impaired by the beverage. Our findings therefore suggest that alcohol diminished cognitive rather than perceptual capacity.